Correlates Corelates of Performance of Athletes in Eastern Samar State University - lacaba, Alvin Bituaran; Lacaba, Teresita Villa Golosino (International Journal of Scientific Research and Management (IJSRM), 2018)
ABSTRACTTitle of Research : Correlates with the Performance of Athletes in the Eastern Samar Samar State University- GuiuanResearcher : Alvin B. LacabaCo-Author : Teresita Villa G. LacabaKeywords; Performance, Coaching skills, Technical skills, Competency, Professional preparation. This study was conducted to Correlates with the Performance of Athletes in the Eastern Samar State University, Guiuan, Specifically, this study answered the following:1. What is the level of competency of the faculty-coaches in terms of:2.1 Professional preparation2.2 Coaching skill 2.3 Technical skill? 2. What is the level of performance of athletes in the sports competition? 3. Is there a significant relationship between : 3.1. level of competency of faculty-coaches, and level of performance of athletes? This study employed descriptive-correlation which involved 30 faculty-coaches in the Eastern Samar Samar State University- Guiuan. Data were retrieved using a survey questionnaire. These were tallied and analyzed using appropriate statistical tools such as percentage, mean, Pearson product-moment correlation.Findings of the study revealed the following information: The competency of the faculty-coaches in terms of professional preparation, coaching skill, and technical skill of the faculty-coaches were all significantly associated to the performance of athletes. Hence, it was deduced that faculty-coaches who rated themselves higher in these criteria can motivate and train better athletes. Based on the findings of this study, the following conclusions are drawn:The faculty-coaches were regarded competent since they were professionally prepared for sports, with very good coaching skill and technically capable to handle their respective event or game. From the findings of the study, the following recommendations are offered:An organized sports training program should be implemented in the school or division so that all faculty-coaches will be given the chances to be trained especially the new ones.Further studies maybe conducted to validate the findings of this study.